(untitled) (Architecture Image Studies, 2026)
Earth dams constructed in seismic areas are very susceptible to the strong ground shaking, particularly when in near-full reservoir conditions that cause increase of system requirement through hydro-mechanical interaction. The present article studies the dynamic response of Al-Adhaim Dam during El-Centro earthquake record (PGA = 0.30 g) at full reservoir level (EL = 143 m) with and without buttressing from high-density polyethylene (HDPE) geogrid during its service life. A fully coupled flow–deformation finite-element formulation was used for the analysis of the seismic displacement, acceleration amplification, stress redistribution, pore-pressure response, seepage behavior and overall stability. Results show that the unretrofitted dam undergoes large seismic-induced deformations of 0.33 m and peak crest acceleration amplifications up to 0.78 g, which result in a well FOS